Beginning C# 2008 Objects - Palmer, Grant (Springer, 2017)
By building from first principles in object–oriented terminology, then advancing through application design with Unified Modeling Language (UML) into practical examples, Beginning C# 2008 Objects: From Concepts to Code provides a foundational guide written from the perspective of two experienced, working authorities on C#. Working coders will benefit from the object–oriented cast of the book and its section on use–case modeling. This is the book to read if you want to deepen and advance your existing professional development in C# with an eye towards advancing out of pure coding work.